Analysis of Community Participation in Sustainable Tourism Development in Simanindo Sub-District - Rara Ayu Rati Kumala Dewi; Nurlisa Ginting (International Journal of Architecture and Urbanism, 2022)
The abundance of natural resources and the expansive beauty of nature make Simanindo a district with great potential for tourism development. This tourism potential was later developed by the Samosir Regency government and used as a sector capable of bringing foreign exchange to the country and society. Tourism development can begin from planning to management or utilization stages and evaluation of results. All these phases are inseparable from the roles and contributions of multiple parties, especially the communities surrounding the tourist destination. This shows that community involvement is an important issue for the success of future tourism development programs. The survey was conducted through a qualitative approach. This study explains and explains the symptoms and trends in the focus of the study. In the first focus, the research method was performed through the collection of key data, and in the second focus, the data was collected through observations, detailed interviews, and focus group discussions. The results of this literature review show that community involvement in tourism progress is influence by internal and external factors that can affect the development of the tourism industry and the standard of living of local communities. The details of this literature study focus on the form of participation and influencing factors, support and hinder the process of community participation in tourism development